Case Report: Primary Breast Diffuse Large B-Cell Lymphoma - Lesmana, Vienna Alodia; Putra, Michael Setiawan; Wirastuti, Elia (Journal of Language and Health, 2025)
Background: Primary breast diffuse large B-cell lymphoma (DLBCL) is a rare entity, accounting for less than 0.5% of all primary breast malignancies and less than 1% of all non-Hodgkin lymphomas. It is often challenging to diagnosed due to its clinical and histopathological resemblance to invasive breast carcinoma. Objective: To report the diagnostic journey and histopathological characteristics of a rare case of primary breast DLBCL and to highlight the importance of immunohistochemical examination in establishing an accurate diagnosis. Methods: This case report documents a 47-year-old female patient presenting with a right breast mass. The diagnosis was established through histopathological examination using Hematoxylin and Eosin (H&E) staining and immunohistochemical analysis. Results: Initial histopathology suggested the possibility of medullary-pattern invasive breast carcinoma with a differential diagnosis of large-cell lymphoma. Immunohistochemical analysis revealed diffuse positive expression of CD20, negative expression of CK5/6 and CD3, and a Ki67 proliferation index exceeding 30%. These findings confirmed the diagnosis of primary breast DLBCL. Conclusion: Primary breast DLBCL is a rare malignancy that should be considered as a differential diagnosis for high-grade breast tumors. Histopathological and immunohistochemical examinations play a crucial role in ensuring an accurate diagnosis. The primary treatment approach involves systemic chemotherapy with or without radiotherapy, while radical mastectomy is not recommended as it may worsen the patient's prognosis. Keywords: Primary breast lymphoma; Diffuse large B-cell lymphoma; Breast tumor; Histopathology; Immunohistochemistry; Case report.